2015
DOI: 10.1108/ecam-04-2014-0048
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors affecting practitioners’ attitudes toward the implementation of an industrialized building system

Abstract: Purpose -An industrialized building system (IBS) is regarded as an effective residential building system that provides several benefits, including high quality, low cost, short time, good flexibility, reduced waste, and strong environmental performance. This system is considered to be valuable in promoting sustainable practices in China, where plans for urbanization have been established. However, the adoption of IBS in China is extremely limited. Potential risks exist and affect the attitudes of practitioners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
166
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(170 citation statements)
references
References 57 publications
4
166
0
Order By: Relevance
“…This was in line with Luo et al [80] who found that there lacked of a quality-supervision mechanism for the production activities, which showed key quality challenges that decreased the assurance among building stakeholders as to the quality of the projects. Inadequate site supervision and improper site decisions were part of the key significant elements influencing project quality on-site.…”
Section: Discussionsupporting
confidence: 87%
“…This was in line with Luo et al [80] who found that there lacked of a quality-supervision mechanism for the production activities, which showed key quality challenges that decreased the assurance among building stakeholders as to the quality of the projects. Inadequate site supervision and improper site decisions were part of the key significant elements influencing project quality on-site.…”
Section: Discussionsupporting
confidence: 87%
“…High capital cost was the most significant barrier to prefabrication development [11,12,29]. This study identified the variables affecting the high capital cost, explored the latent factors, developed the FAEM, conducted case application and then reduce the capital cost.…”
Section: Discussionmentioning
confidence: 99%
“…Design diversity, aesthetics, maintenance complexity and quality impression also affect the initial cost [12,29,30]. Meanwhile, supply chain issues and lack of codes and standards contributed to high cost [10,12,29]. Chua et al revealed the cost of mold usage and replacement had an impact on prefabrication cost [31].…”
Section: Cost Incrementsmentioning
confidence: 99%
See 2 more Smart Citations